ODI <25 Denotes Patient Acceptable Symptom State After Minimally Invasive Lumbar Spine Surgery. Issue 3 (1st February 2023) - Shahi, Pratyush; Shinn, Daniel; Singh, Nishtha; Subramanian, Tejas; Song, Junho; Dalal, Sidhant; Araghi, Kasra; Melissaridou, Dimitra; Sheha, Evan; Dowdell, James; Qureshi, Sheeraz A.; Iyer, Sravisht
Abstract : Study Design: Retrospective review of prospectively collected data. Objective: To determine the Oswestry Disability Index (ODI) cutoff for achieving Patient Acceptable Symptom State (PASS) at one year following minimally invasive lumbar spine surgery. Summary of Background Data: An absolute score denoting PASS, rather than a change score denoting minimal clinically important difference (MCID), might be a better metric to assess clinical outcomes. Materials and Methods: Patients who underwent primary minimally invasive transforaminal lumbar interbody fusion or decompression were included. The outcome measure was ODI. The anchor question was the Global Rating Change: "Compared with preoperative, you feel (1) much better, (2) slightly better, (3) same, (4) slightly worse, or (5) much worse." For analysis, it was collapsed to a dichotomous outcome variable (acceptable=response of 1 or 2, unacceptable=response of 3, 4, or 5). Proportion of patients achieving PASS and the ODI cutoff using receiver operating characteristic curve analyses were assessed for the overall cohort as well as subgroups based on age, sex, type of surgery, and preoperative ODI. Differences between the PASS and MCID metrics were analyzed. Results: A total of 137 patients were included. In all, 87% of patients achieved PASS. Patients less than or equal to 65 years and those undergoing fusion were more likely to achieve PASS. The receiver operating characteristic curve analysis revealed an ODI cutoff of 25.2 to achieve PASS (area under the curve: 0.872, sensitivity: 82%, specificity: 83%). The subgroup analyses based on age, sex, and preoperative ODI revealed area under the curve >0.8 and ODI threshold values consistent between 25.2 and 25.5 (except 28.4 in patients with preoperative ODI >40). PASS was found to have significantly higher sensitivity compared with MCID (82% vs. 69%, P =0.01). Conclusions: Patients with ODI <25 are expected to achieve PASS, irrespective of age, sex, and preoperative disability. PASS was found to have significantly higher sensitivity than MCID. Level of Evidence: 3.